Malignant atrophic papulosis treated with eculizumab and hirudin: a fatal case report and literature review - Yu, Linna; Wang, Yun; Tang, Xiaodan; Zhao, Xueru; Song, Zhengji (Frontiers in Cardiovascular Medicine, 2024)
Background Malignant atrophic papulosis (MAP) is a rare obliterative vasculopathy whose etiology and pathophysiological mechanisms remain unknown, and the treatment is still empirical. It can involve multiple systems, especially the gastrointestinal tract and central nervous system, and has a poor prognosis. Case presentation A 20-year-old Chinese male appeared to have Widespread atrophic papules and plaques, intermittent abdominal pain, recurrent bowel perforation, and psoas abscess. The clinical diagnosis of MAP was supported by skin biopsy. He was then treated with anticoagulants, antiplatelets, glucocorticoids, and immunosuppressants and started on eculizumab and hirudin after the first surgical interventions. Despite the aggressive immunosuppression, anticoagulant, antiplatelet, humanized monoclonal antibodies, and surgery therapy, he died five months after presentation. Conclusions MAP is an extremely rare obliterative vasculopathy manifesting as benign cutaneous involvement or potentially malignant systemic involvement. MAP patients who exhibit any abdominal symptoms should undergo laparoscopy and evaluation in time and start on eculizumab and treprostinil as soon as possible, as the combination of them is presently the most effective treatment option for gastrointestinal MAP and hopefully reduce mortality.